Perubahan Sosial Masyarakat Sebagai Dampak Didirikannya RA Darussalam di Desa Wonoharjo - Salsa Fadilla; Siti Hazar Agisah; Eha Sholehah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
Raudhatul Athfal is an early childhood education unit under the guidance of the Kementrian Agama. That way, it can make it easier to educate children and introduce Islamic teachings that are suitable for their children to school. The emergence of RA, which was mostly founded by Islamic-based institutions, whether Islamic mass organizations or other Islamic missionary institutions, is expected to have an influence on society, both social and religious life. Therefore by using qualitative methods. This research aims to describe the social changes in society as a result of the establishment of RA Darussalam in Wonoharjo Village. The research results show that before the establishment of RA Darussalam in Wonohrajo Village, the local community was reluctant to send their children to early childhood education due to the long distance between schools and family economic problems. However, after the founding of RA Darussalam, public interest in sending children to early childhood education institutions increased, which ultimately had an impact on the social conditions of the surrounding community. Apart from that, the establishment of RA Darssalam was also able to increase the level of community welfare through Darussalam Mart, which is a simple shop that provides the opportunity for parents of students or the surrounding community to leave their goods for sale at Darussalam Mart. Therefore, RA Darussalam not only has a social impact, but also an economic impact for the people of Wonoharjo Village.